Walker. The final season [videorecording (DVD)] - VandenBos, Bret; Willer, Brandon; Carew, Aaren; Johnson, Blythe Ann; Fisher, Casey; Liberatore, Lindsay; Padalecki, Jared, 1982-; Morgan, Lindsey, 1990-; Allen, Keegan, 1989-; Pileggi, Mitch (Paramount, 2024)
In the Final Season, it's a season of change for Cordell Walker as his children flee the nest, a relationship with Geri takes hold, and turmoil finds the Texas Ranger. But as Walker struggles to accept this new future, a gruesome serial killer from the past threatens to upend his life and the lives of those he loves. See how it all unfolds with this 3-disc DVD collection that includes every episode plus exclusive deleted scenes and gag reel.